2015
DOI: 10.1111/jfpp.12623
|View full text |Cite
|
Sign up to set email alerts
|

Storage Stability of Carotenoids in Paprika from Conventional, Organic and Frost-Damaged Spice Red Peppers as Influenced by Illumination and Antioxidant Supplementation

Abstract: Response of natural colorants in paprika from conventional, organic and frostdamaged spice peppers to illumination of 2,000, 4,000 and 6,000 lux was studied. The impact of antioxidant supplementation on color retention in such products was also aimed. During 12 months of storage in the dark, the paprika from conventional, organic and frost-damaged peppers lost 60.2, 99.7 and 79.3 ASTA units, respectively. The tocopherol supplementation retarded carotenoid degradation by 28, 32 and 40% in paprika from conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…Manzocco et al (2012) They presented a model which integrated the effect of both accelerating factors. Similar studies to these already mentioned have been applied to honey (Boonchiangma, Chanthai, Srijaranai, & Srijaranai, 2011), jujube fruit (Jiang, Zheng, & Lu, 2014) and paprika (Koncsek, Kruppai, Helyes, Bori, & Daood, 2016). In all these publications the degradation of color or other factors over storage time due to different illumination conditions were measured chemically or physically, but not by sensory analysis.…”
Section: Introductionmentioning
confidence: 87%
“…Manzocco et al (2012) They presented a model which integrated the effect of both accelerating factors. Similar studies to these already mentioned have been applied to honey (Boonchiangma, Chanthai, Srijaranai, & Srijaranai, 2011), jujube fruit (Jiang, Zheng, & Lu, 2014) and paprika (Koncsek, Kruppai, Helyes, Bori, & Daood, 2016). In all these publications the degradation of color or other factors over storage time due to different illumination conditions were measured chemically or physically, but not by sensory analysis.…”
Section: Introductionmentioning
confidence: 87%
“…A powder of spice red pepper, a type of organic paprika, exhibited low stability of colorants during storage in dark conditions, and under illumination; however, supplementation with tocopherol retarded degradation of carotenoids and color of these samples when stored in dark (Koncsek, Kruppai, Helyes, Bori, & Daood, 2016). Howard et al (2000) reported that vitamin E in the pericarp tissue of 32 pepper accessions studied, αand β-tocopherols varied between the accessions but αtocopherol was always the predominant form; and provitamin A levels ranged from traces to 18.52 mg/100 g fresh weight (Baenas, Belović, Ilic, Moreno, & García-Viguera, 2019;Bortolin et al, 2016).…”
Section: Vitamins and Minerals Among Other Componentsmentioning
confidence: 99%
“…A powder of spice red pepper, a type of organic paprika, exhibited low stability of colorants during storage in dark conditions, and under illumination; however, supplementation with tocopherol retarded degradation of carotenoids and color of these samples when stored in dark (Koncsek, Kruppai, Helyes, Bori, & Daood, 2016).…”
Section: Biochemical Compositionmentioning
confidence: 99%
“…However, differences in the carotenoid degradation between both oleoresins were not statistically significant (P=0.570). The total carotenoid degradation is a big quality problem in paprika and chili powder because it is strongly related with color loss; the addition of other antioxidant molecules (such as tocopherols or BHT) is recommended (Koncsek et al, 2016). Moreover, in avocado oil the natural presence of tocopherols acts as a natural antioxidant (Berasategui et al, 2012).…”
Section: Sample T (°C)mentioning
confidence: 99%